2008
DOI: 10.1007/s00726-008-0055-4
|View full text |Cite
|
Sign up to set email alerts
|

Human prolidase and prolidase deficiency: an overview on the characterization of the enzyme involved in proline recycling and on the effects of its mutations

Abstract: Here we summarized what is known at the present about function, structure and effect of mutations in the human prolidase. Among the peptidases, prolidase is the only metalloenzyme that cleaves the iminodipeptides containing a proline or hydroxyproline residue at the C-terminal end. It is relevant in the latest stage of protein catabolism, particularly of those molecules rich in imino acids such as collagens, thus being involved in matrix remodelling. Beside its intracellular functions, prolidase has an antitox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
114
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(119 citation statements)
references
References 90 publications
0
114
1
4
Order By: Relevance
“…Prolidase has a major role in the recycling of proline released during the degradation of collagen and dietary proteins [11]. Although there is considerable knowledge concerning the putative roles of the prolidase enzyme [12], the pathophysiology of PD remains an enigma.…”
Section: Discussionmentioning
confidence: 99%
“…Prolidase has a major role in the recycling of proline released during the degradation of collagen and dietary proteins [11]. Although there is considerable knowledge concerning the putative roles of the prolidase enzyme [12], the pathophysiology of PD remains an enigma.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the carbohydrate-deficient transferrin studies were tested and found negative, ruling out congenital disorders of glycosylation. Notably, SLE has been linked to PD [Bissonnette et al, 1993;Shrinath et al, 1997;Di Rocco et al, 2007] and is associated with multiple mutations [Lupi et al, 2006[Lupi et al, , 2008Falik-Zaccai et al, 2010;Klar et al, 2010;Butbul Aviel et al, 2012]. The mechanistic relationship between these entities is not clear, but a loss of immune tolerance to lupus-associated autoantigens in PD has been hypothesized, leading to positive antinuclear antibodies and other autoantibody testing even in patients without clinical SLE [Kurien et al, 2013].…”
Section: Discussionmentioning
confidence: 99%
“…To date, ∼ 90 patients with PD have been described, 67 of which have been molecularly characterized revealing 28 distinct mutant alleles [Tanoue et al, 1990[Tanoue et al, , 1991Ledoux et al, 1994Ledoux et al, , 1996Kikuchi et al, 2000;Forlino et al, 2002;Lupi et al, 2004Lupi et al, , 2006Lupi et al, , 2008Hershkovitz et al, 2006;Wang et al, 2006;Falik-Zaccai et al, 2010;Klar et al, 2010;Butbul Aviel et al, 2012;Caselli et al, 2012;Pandit et al, 2013;Besio et al, 2015]. The PEPD gene is over 130 kb long and is comprised of 15 exons.…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme has a major role in the recycling of proline released during the degradation of collagen and dietary proteins [Lupi et al, 2004]. Although there is considerable knowledge concerning the putative roles of the prolidase enzyme [Lupi et al, 2008], the pathophysiology of PD remains an enigma.…”
Section: Introductionmentioning
confidence: 99%